The effect of sonication on the ion exchange constant, KXBr of CTABr/chlorobenzoates micellar systems - Nor Saadah Mohd Yusof (Ultrasonics Sonochemistry, 2021)
The ion exchange constant, KXBr (for the case of cetyltrimethylammonium bromide, CTABr, in this study) is a method dependant characterization of ion exchange process by counterions, X and Br with different relative binding ratios. In this report, the ion exchange constant, KXBr values for micelle systems irradiated under 2 min of sonication at 120 W power using a probe sonicator with 1 cm tip were determined to be 85.2, 125.6 and 122.4 when X  = o-, m- and p-chlorobenzoates, respectively. The values were quantified using a semiempirical kinetic method coupled with Pseudophase Micellar model, and later compared to the same system in the absence of sonication. The sonication was found to amplify the KXBr values by ~ 13-fold for X  = o-chlorobenzoate and ~ 2.5-fold for X  = m- and p-chlorobenzoates. This is due to the improvement of ion exchange process by the oscillation of bubbles generated by acoustic cavitation. An active ion exchange process indicates better stabilization of the micelle aggregational structure by the penetration of the introduced counterions, X into the micelle Stern layer leading to the growth of the micelle. This is supported by the remarkable increase in the viscosity of the micelle system by > 7-fold for X  = o-chlorobenzoate and by > 2-folds for X  = m- and p-chlorobenzoates. Sonication was also found to induce maximum viscoelasticity at lower concentration ratio of [CTABr]:[X]. The ability of ultrasound to induce micelle growth and exhibiting viscoelasticity at lower concentration of counterionic additive will be very useful in technologies where viscoelastic solution is desired such as in oil drilling and centralized heating and cooling system.